2019
DOI: 10.1111/iej.13132
|View full text |Cite
|
Sign up to set email alerts
|

Retreatability of two hydraulic calcium silicate‐based root canal sealers using rotary instrumentation with supplementary irrigant agitation protocols: a laboratory‐based micro‐computed tomographic analysis

Abstract: Aim To investigate the retreatability of two calcium silicate‐based materials (BioRoot RCS, Septodont, Saint–Maur‐des‐Fossés, France and GuttaFlow Bioseal, Colténe/Whaledent AG, Langenau, Germany) using rotary instrumentation combined with supplementary irrigant agitation techniques using extracted teeth in a laboratory setting. Methodology The root canals of extracted single‐rooted mandibular premolars were prepared to size 40, .04 taper and randomly divided into two experimental groups (n = 36) depending on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 55 publications
4
32
0
5
Order By: Relevance
“…It was observed that some studies adopted one point of the root, usually 5 mm from the anatomical apex, and measure the width of the root canal in both buccal and proximal directions, following the methodology of Wu et al (2000), to determine its shape (Tinoco et al 2014, Teixeira et al 2015, Lee et al 2019). In other studies, specimens are allocated from the same group of teeth by randomization (Topçuoğlu et al 2016, Silva et al 2017, Pedullà et al 2019), whilst some of them adopted a combination of radiographic and randomized methods to form pairs (Ruckman et al 2013, Bernardes et al 2016). Recently, a few studies started to use specific anatomical parameters identified by means of a micro‐CT scanning to pair‐matched samples (Versiani et al 2013b, Johnsen et al 2016, Versiani et al 2016b, Johnsen et al 2017, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that some studies adopted one point of the root, usually 5 mm from the anatomical apex, and measure the width of the root canal in both buccal and proximal directions, following the methodology of Wu et al (2000), to determine its shape (Tinoco et al 2014, Teixeira et al 2015, Lee et al 2019). In other studies, specimens are allocated from the same group of teeth by randomization (Topçuoğlu et al 2016, Silva et al 2017, Pedullà et al 2019), whilst some of them adopted a combination of radiographic and randomized methods to form pairs (Ruckman et al 2013, Bernardes et al 2016). Recently, a few studies started to use specific anatomical parameters identified by means of a micro‐CT scanning to pair‐matched samples (Versiani et al 2013b, Johnsen et al 2016, Versiani et al 2016b, Johnsen et al 2017, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, experimental groups in comparative studies have been created by selecting randomized either single‐ or multi‐rooted teeth with limited sample size (Topçuoğlu et al 2016, Silva et al 2017, Pedullà et al 2019). In practice, this means a very poor standardization and the inability to ensure experimental comparability as it may yield experimental groups with large variations in the baseline of the substrate (Smith & Steiman 1994, També et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the conventional syringe final irrigation protocol reduced significantly the amount of the remaining filling material indicating its importance in the retreatment protocol. Recent studies pointed out that supplementary irrigation with agitation techniques enhanced the removal of filling material (Suk et al 2017, Silveira et al 2018, Pedullà et al 2019). However, additional studies are necessary to evaluate whether there is an activated irrigation technique capable of compensating for the limitations of mechanical preparation and resulting in similar filling removal as in larger instrumentation.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the abundance of previous research that demonstrates the limitations of basic instrumentation for the removal of filling material from the root canal, newer approaches are currently being investigated in the hope of improving the filling remnant removal. Numerous activated irrigation techniques have been proposed as adjunct treatment protocols to follow mechanical retreatment, such as ultrasonically activated irrigation (Bernardes et al 2016, Pedullà et al 2019), sonic‐activated irrigation (Kaloustian et al 2019) and laser‐activated irrigation (Suk et al 2017). To date, few studies have evaluated the additional steps of instrumentation using various adjustable instruments (Self‐adjusting File, ReDentNova, Berlin, Deutchland; XP‐endo Shaper and Finisher, FKG, La Chaux de Fonds, Switzerland; and TRUShape, Dentsply Sirona, Ballaigues, Switzerland).…”
Section: Introductionmentioning
confidence: 99%
“…One of the gold-standard agitation techniques is the use of ultrasonic instruments 18 . Despite this, their effectiveness for filling removal shows contradictory results 19 21 . Mechanical agitation driven by novel finishing instruments like XP-endo Finisher R (FKG Dentaire, La Chaux-de-Fonds, Switzerland), specifically developed to boost cleaning during retreatment, were shown to improve the filling removal 15 , 22 24 .…”
Section: Introductionmentioning
confidence: 99%